Xenoschesis Förster (Hymenoptera: Ichneumonidae) parasitizing webspinning and leafrolling sawflies with descriptions of four new species and a key to Chinese species - Sheng, Mao-Ling; Sun, Shu-Ping; Wang, Tao (Zootaxa, 2013)
Seven species of Xenoschesis Förster, 1869, are reported from China. Four species, X. (Polycinetis) inareolata Sheng & Sun, sp. n. from Liaoning Province, X. (Polycinetis) truncata Sheng & Sun, sp. n. from Liaoning, Jilin and Henan Prov-inces, X. (Xenoschesis) tianzhuensis Sheng & Sun, sp. n. and X. (Xenoschesis) weii Sheng & Sun, sp. n. collected in Anhui Province are new to science. One, X. (Xenoschesis) fulvipes (Gravenhorst) was reared from Acantholyda parki Shinohara & Byun and A. posticalis Matsumura, is new record for China. Xenoschesis (Xenoschesis) crassicornis Uchida was reared from A. erythrocephala (L.) and A. parki Shinohara & Byun. A key to species of Xenoschesis Förster known inChina is provided.